Assessing Divergence and Convergence in French and German Strategic Narratives - Huntley, Matthew David (2025)
At the core of this research is a comparative study designed to determine whether the strategic narratives of France and Germany regarding European defence cooperation are currently exhibiting divergence or convergence. Despite evidence of the previous differing approaches and preferences of the two countries towards European defence cooperation, the findings reveal that the current trend is moving towards more convergence, despite persistent unit-level factors that continue to generate elements of divergence. The system-level catalysts for this overall convergence are numerous, but Russia’s aggressive expansionism coupled with China’s perceived efforts to reshape the international order play a substantial role. The unit-level factors responsible for the persistent elements of divergence between French and German strategic narratives are to be found mainly in the two countries’ differing strategic cultures and levels of executive autonomy.